L’affirmation de la géographie quantitative française au cœur d’un moment d’ébullition disciplinaire (1972-1984) - Sylvain Cuyala (Bulletin de l’Association de Géographes Français)
The 1970s were a period of heavy turbulence in French geography. During this decade, the “New Geography” emerges, and one of its forms is the “theoretical and quantitative geography”. The aim of this article is to analyse the emergence of this geography by means of a sociological theory (scientific/intellectual movement) (Frickel, Gross, 2005), combined with spatial analysis. Temporal evolution and spatial configuration of this scientific movement remained largely unknown until now. This paper mainly engages archives (Répertoire des géographes, journals or lists of communications of TGQ colloquium) analyzed with quantitative methods (from graph theory to the analysis of geographical units’ specialization). This investigation has shown that the emergence of this scientific movement took place from 1971-1972 to 1984, involving a small number of actors and locations, and while individual researchers interact in order to give themselves a self training.